2021
DOI: 10.1097/wno.0000000000001297
|View full text |Cite
|
Sign up to set email alerts
|

Bruch Membrane Opening Minimum Rim Width in Neuromyelitis Optica

Abstract: Background: Optical coherence tomography (OCT) analyzes the neurodegeneration in neuromyelitis optica (NMO) and multiple sclerosis (MS) and quantifies optical atrophy. The retinal nerve fiber layer (RNFL) and ganglion cell layer (GCL) thickness are decreased, and this structural change is correlated with visual function of patients, including contrast vision and visual field deviation. The main objective of this study was to evaluate the Bruch membrane opening minimum rim width (BMO) of the patients with NMO. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Several longitudinal clinical studies on MS demonstrated a reduction in the mean, superior, inferior, and temporal retinal nerve fiber layer (RNFL) (11), the TRV, mRNFL, GCIPL (12) and the mGCIPL and peripapillary retinal nerve fiber layer (pRNFL) (13) thicknesses by OCT over time.…”
Section: Discussionmentioning
confidence: 99%
“…Several longitudinal clinical studies on MS demonstrated a reduction in the mean, superior, inferior, and temporal retinal nerve fiber layer (RNFL) (11), the TRV, mRNFL, GCIPL (12) and the mGCIPL and peripapillary retinal nerve fiber layer (pRNFL) (13) thicknesses by OCT over time.…”
Section: Discussionmentioning
confidence: 99%
“…Leaney et al 155 , obtiveram resultados semelhantes, mas a amostra incluiu neuropatias ópticas variadas no mesmo grupo, não distinguindo por etiologia. A literatura ainda apresenta o uso da LMR na avaliação de neuropatia óptica isquêmica anterior [156][157][158][159] , neurite óptica por esclerose múltipla ou neuromielite óptica [160][161][162] e neuropatia óptica traumática 163 . Não há nenhum estudo publicado especificamente voltado para a compressão quiasmática, até o momento do desenvolvimento desta tese.…”
Section: A Tomografia De Coerência óPtica Como Ferramenta úTil Na Ava...unclassified